SYNTHESIS OF CdS NANOPARTICLES BY CHEMICAL Co-PRECIPITATION METHOD AND ITS COMPARATIVE ANALYSIS OF PARTICLE SIZE VIA STRUCTURAL AND OPTICAL CHARACTERIZATION - Ali, Syed Kaabir; Wani, Henna; Upadhyay, Chandramani; Sai Madhur, K.S.S.N.; Khan, Imran; Gul, Sabia; Jahan, Nushrat; Ali, Firdaus; Hussain, Salim; Azmi, Kashif (Indonesian Physical Review, 2020)
CdS is an important wide bandgap chalcogenides most popularly studied for various optoelectronics and biosensing applications. In this study, CdS Nanoparticles (NPs) have been prepared successfully by chemical co-precipitation method, using cadmium acetate and sodium sulphide as precursors. A comparative study of average particle size calculated by Scherrer Plot, Uniform Deformation Model (UDM), Dynamic Light Scattering (DLS) analysis and Brus Model has been done here. The structural and optical behaviour of synthesized samples were investigated via X-ray diffraction (XRD), DLS and UV–Visible Spectroscopy. The XRD spectra of the prepared CdS NPs revealed the crystalline phase having cubic structure. The average particles size has been studied via Debye Scherrer equation and Scherrer Plot. For the theoretical calculations of particle size along with the induced lattice strain, considering the broadening effect of lattice strain, Williamson-Hall analysis was employed. Assuming the lattice strain to be isotropic in nature, UDM was applied for calculation. The particles size distribution profile in terms of volume as well as intensity was recorded using DLS analysis in ethanol medium at room temperature. Besides this, the energy bandgap was obtained by applying Tauc model in the recorded absorption spectra. The obtained value of bandgap was used in Brus model for estimating the average particle size. The obtained comparative results show that the average particle size of the prepared CdS NPs estimated from Scherrer equation, Scherrer plot, UDM plot and Brus model are almost similar and lies in the range of 2-5 nm whereas the results of DLS showed wide variation in the range of 40-600 nm.